2016
DOI: 10.1007/s10802-016-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational Psychotherapy and Omega-3 Supplementation Improve Co-Occurring Behavioral Problems in Youth with Depression: Results from a Pilot RCT

Abstract: This pilot randomized controlled trial (RCT) investigated benefits of omega-3 fatty acid supplementation and Individual-Family Psychoeducational Psychotherapy (PEP; a family-focused, cognitive-behavioral therapy) for behavior problems among youth with depression. Participants aged 7–14 with DSM-IV-TR depressive disorders (N = 72; 56.9% male) were randomized to 1 of 4 treatment conditions: PEP + omega-3, PEP monotherapy (with pill placebo), omega-3 monotherapy, or placebo (without active intervention). At scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Thirty-six studies were published in order to evaluate the efficacy of EPA and DHA in mild and moderate unipolar depression [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91]. Among these, eight were performed in women with perinatal depression [58,64,66,68,71,81,82,88].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-six studies were published in order to evaluate the efficacy of EPA and DHA in mild and moderate unipolar depression [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91]. Among these, eight were performed in women with perinatal depression [58,64,66,68,71,81,82,88].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, eight were performed in women with perinatal depression [58,64,66,68,71,81,82,88]. Three studies were conducted in adolescents [62,86,87] and three trials in elderly depressive patients [72,73,75]. To limit the heterogeneity of this review, we decided to exclude trials on the efficacy of PUFAs in treating MDD in subjects with medical comorbidity and trials in which depressive symptoms were secondary to dementia and other neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent number of studies investigated the role of PUFAs in the treatment of major depressive disorder (MDD). Although some of them [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] found no significant data, several trials [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] showed an improvement of depressive symptoms in patients treated with n-3 PUFAs in combination with antidepressants. In particular, a combination of higher dose of EPA with lower dose of DHA (EPA 1.67 g/day + DHA 0.83 g/day), added to existing antidepressant treatment, revealed beneficial effects on mood [102,103].…”
Section: Affective Symptomsmentioning
confidence: 99%
“…Both are reliable and valid measures (Young et al 1978;Poznanski et al 1984;Fristad et al 1992Fristad et al , 1995Youngstrom et al 2003). (For a thorough discussion of ''filtered'' versus ''unfiltered'' ratings, see Yee et al 2015).…”
Section: Study Assessmentsmentioning
confidence: 99%